ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS SISWA SMA KELAS XI - Sri Rizki Hardianti; Kiki Nia Sania Effendi (IKIP Siliwangi, 2021)
This research aims to determine the mathematical representation ability of students in class XI of High School. The subject of this study were students of class XI MIPA 2 in a high school in Jatisari sub-district, Karawang Regency. The method and the approach that is used in this research is the descriptive method with a qualitative approach. The instrument in this research was a test instrument of mathematical representation ability with linear progam material as many as 3 items. Data analysis techniques used in this research consisted of data reduction, data presentation, and drawing concluding. The result of this research were in the high category there were 4 students with an 18,18% percentage, in the medium category, there were 12 students with a 54,54% percentage, and in the low category 6 students were in the low category with a 27,28% percentage. It can be concluded that the mathematical representation ability of class XI MIPA 2 students in that school on the linear progam material is in the medium category.